Las instituciones en el conflicto por el empleo en la industria petrolera caso Barrancabermeja: análisis del decreto 1668 de 2016 (2020)
The document analyses the role played by formal and informal institutions involved in the conflict over employment in the oil sector in Barrancabermeja (Santander) since the expedition of decree 1668 of 2016. The study is supported by Elinor 0strom's framework of Institutional Analysis and Development IAD which identifies the impact that institutional arrangements have on actors' behaviors and decision-making. One of the main findings is that the dismantling of an informal institutional arrangement of operational type to establish a centralized model of constitutional order is in transition and has generated resistance from actors who mobilize resources and create new institutions in their adaptation process. The results want to provide recommendations to the review process of the law that is being carried out by the Ministry of Labor and contribute to studies on informal institutions as a fundamental part of the public policy approach in Colombia.